The Daily Telegraph Century of Sport : Great Sporting Events and Personalities of the Twentieth Century - Edited by Welch, David (London Macmillan Publishers, 1998)
A century of sports events and achievement from around the world in eyewitness accounts, quotes and analysis, with archive pictures of the greatest sporting moments ever. It includes year-by-year highlights of significant sporting news stories, sports first and lasts and biographies of the century's great sporting heroes
Include Color Illustration and Index
Keywords: Sports